Términos de intercambio y la actividad económica del Perú: 2002 - 2013 - Ventura Aguilar, Henry Elder (2014)
In the present research the behavior of the terms of trade and the level of economic activity of the Peruvian economy has been evaluated, with the purpose of identifying the effects of the terms of trade in the national economy, in order to contribute to explain their relationship and thus serve for the design of economic policies. The research has been developed based on the information provided by statistical reports of the Central Reserve Bank of Peru and the National Institute of Statistics and Informatics. The procedure followed in the investigation was first to compile and process the information of the terms of trade, the real Gross Domestic Product, among other variables of interest; the respective descriptive statistics were then determined. Then, to determine the impact of terms of trade on economic activity, the following econometric model was estimated, PBI = β0 + β1TI + μi, in this model a structural break was identified, which with econometric techniques overcame the instability of The estimators and the serial correlation, arriving to finally determine the econometric model statistically significant. It is concluded that there is empirical evidence that the terms of trade have positive effects on the domestic economy activity, the regression estimators show that they are directly related, so that as the terms of trade increase, the national economy favored.